EFFECTIVENESS OF IT AS POST PROBLEM MODEL ON STUDENT CRITICAL THINKING ABILITY IN SMA GEOGRAPHY LESSONS - Zulkarnain Zulkarnain; Listumbinang Halengkara; Fania Dwi Silvi (Journal Learning Geography, 2020)
This research aims to analyze (1) the differences of students critical thinking skills using problem posing models and conventional models, (2) the differences of students critical thinking skills before and after using problem posing models and conventional models, and (3) the effectiveness of the problem posing model towards students critical thinking skills of geography subject in XI Social Science class of SMAN 13 Bandar Lampung. This research uses quasi-experimental with cross design. The subjects of this research are students in XI Social Science class of SMAN 13 Bandar Lampung. Data collection techniques in this research use tests and documentation, while data analysis techniques that are used in this research are Two Way Variants (ANOVA), and Effect Size. The results indicate that there are differences in students' critical thinking skills after studying with problem posing models and conventional models. The differences are tested by two way variance analysis and the result of sig value is 0.009 0 , 05 . The result also indicates that the problem posing model is more effective for improv students critical thinking skills of geography subjects in XI Social Science class of SMAN 13 Bandar Lampung.Penelitian ini bertujuan untuk menganalisis (1) Perbedaan kemampuan berpikir kritis siswa menggunakan model problem posing dengan model konvensional, (2) Perbedaan kemampuan berpikir kritis siswa sebelum dan sesudah menggunakan model problem posing dengan model konvensional, dan (3) Efektivitas model problem posing terhadap kemampuan berpikir kritis siswa pada mata pelajaran geografi kelas XI IPS SMA Negeri 13 Bandar Lampung. Penelitian ini menggunakan eksperimen semu dengan desain cross. Subjek penelitian ini adalah siswa kelas XI IPS SMA Negeri 13 Bandar Lampung. Teknik pengumpulan data dalam penelitian menggunakan tes dan dokumentasi, sedangkan teknik analisis data yang digunakan dalam penelitian ini adalah Varian Dua Jalan (ANOVA), dan Effect Size. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan berpikir kritis siswa setelah belajar dengan model problem posing dan model konvensional. Perbedaan diuji dengan analisis varian dua jalan dan hasil nilai sig. adalah 0,0090,05. Hasil penelitian juga menunjukkan bahwa model problem posing lebih efektif untuk meningkatkan kemampuan berpikir kritis siswa pada mata pelajaran geografi kelas XI IPS SMAN 13 Bandar Lampung.